2014
DOI: 10.1002/psc.2665
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, and biological activity of poly(arginine)-derived cancer-targeting peptides in HepG2 liver cancer cells

Abstract: The solid-phase synthesis, structural characterization, and biological evaluation of a small library of cancer-targeting peptides have been determined in HepG2 hepatoblastoma cells. These peptides are based on the highly specific Pep42 motif, which has been shown to target the glucose-regulated protein 78 receptors overexpressed and exclusively localized on the cell surface of tumors. In this study, Pep42 was designed to contain varying lengths (3-12) of poly(arginine) sequences to assess their influence on pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 48 publications
(115 reference statements)
0
24
0
Order By: Relevance
“…Varying lengths of arginine-based Cell Penetrating Peptides (CPPs) have been used for intra-cellular delivery of drugs and genetic materials [57, 58]. It has been observed that peptides of six or more arginine (or guanidinium groups) were necessary for uptake into the cells.…”
Section: Discussionmentioning
confidence: 99%
“…Varying lengths of arginine-based Cell Penetrating Peptides (CPPs) have been used for intra-cellular delivery of drugs and genetic materials [57, 58]. It has been observed that peptides of six or more arginine (or guanidinium groups) were necessary for uptake into the cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, optimal coupling conditions may not be easily found, which may be exacerbated by the bulky 2,2,4,6,7-pentamethyldihydrobenzofurane (Pbf) protecting group commonly used for arginine during solid-phase synthesis (26). Further, solution-phase coupling schemes would likely require subsequent purification by HPLC (27, 28), while the reaction itself can be complicated by the high charge density and secondary structures displayed by poly-Arg (29, 30). …”
Section: Resultsmentioning
confidence: 99%
“…These types of amphiphilic peptides have been shown to aggregate during the course of peptide synthesis on the non-polar polystyrene-based resins causing diminished purities and yields [5]. Therefore, the polar poly (ethylene) glycol (PEG) resin which was shown to afford excellent crude purities and yields of synthetically challenging amphiphilic peptide sequences was adopted for our solid-phase synthesis strategy [6] (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
“…Chlorobenzotriazol-1-yl)-N,N,Nâ€Č,Nâ€Č-tetramethyluronium hexafluorophosphate, HCTU, as activator and coupling reagent, N-methylmorpholine, NMM, as base in N,N-dimethylformamide, DMF, as solvent for the coupling reactions [5]. The deprotection steps of the fluorenylmethoxycarbonyl, Fmoc, group were completed with piperidine in DMF.…”
Section: Peptide Synthesis Was Conducted On a Psi 200c Peptide Synthementioning
confidence: 99%